IMPLEMENTASI VISUAL BRANDING PADA AKUN INSTAGRAM TRIBUN EO BOGOR (@TRIBUNEOBOGOR) MELALUI DESAIN KONTEN HARI BESAR - El Azmi, Tsabita; Tri Harpin Pranata, Rici (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of visual branding on the Instagram account of Tribun EO Bogor (@tribuneobogor) through the redesign of momentum and holiday content, and to describe the application of visual elements in building a visual identity for digital media. The research uses a qualitative descriptive method with data collection techniques including observation, documentation, literature study, and active participation. The object of the study focuses on the Instagram account of Tribun EO Bogor (@tribuneobogor) by comparing the visual appearance before and after the redesign. The analysis is based on the concepts of visual branding and visual design principles, including unity, balance, emphasis, and rhythm. The results show that the visual appearance of the account before the redesign still exhibited inconsistencies in the use of color, typography, layout, logo size, and social media information templates, so the account's visual identity had not been optimally formed. The redesign produced a more structured and consistent appearance through the application of a dominant blue color palette aligned with the visual identity of Tribunnews Bogor, a neater layout, and the use of uniform information templates for each post. The application of visual design principles supports compositional order and clarifies the delivery of information in social media content. The implementation of visual branding through consistent management of design elements strengthens the visual identity of the Tribun EO Bogor Instagram account as a local digital media, resulting in a more professional, recognizable, and representative appearance.